А) (3 - 2x)² = 9 - 12x + 4x² || 4)
Б) (3 - 2х)(3 + 2х) = 9 - 4х² || 2)
В) (3 - 2х)(9 + 6x + 4x²) = 27 - 8х³ || 3)
Г) (3 - 2х)³ = 27 − 54x + 36x² - 8x³ || 1)
Объяснение:
А)(3−2x)²; 4)9−12x+4x².
B)(3−2x)(3+2x); 2)9−4x²;
В)(3−2x)(9+6x+4x²); 3)27−8x³;
Г)(3−2x)³; 1)27−54x+36x²−8x³
А) (3 - 2x)² = 9 - 12x + 4x² || 4)
Б) (3 - 2х)(3 + 2х) = 9 - 4х² || 2)
В) (3 - 2х)(9 + 6x + 4x²) = 27 - 8х³ || 3)
Г) (3 - 2х)³ = 27 − 54x + 36x² - 8x³ || 1)
Объяснение:
А)(3−2x)²; 4)9−12x+4x².
B)(3−2x)(3+2x); 2)9−4x²;
В)(3−2x)(9+6x+4x²); 3)27−8x³;
Г)(3−2x)³; 1)27−54x+36x²−8x³